Effect of Manual Traffic Control on Evacuation Time Estimates. Issue 9 (September 2020) - Parr, Scott A.; Herrera, Nelida; Wolshon, Brian; Smith, Todd
Manual traffic control (MTC) is a common intersection control strategy where trained personnel, typically police law enforcement officers, allocate intersection right-of-way to approaching vehicles. MTC is frequently used for special events and during emergencies. However, the current state-of-the-practice has shown little research that quantifies or assesses the benefits of MTC during evacuations. This paper describes research to develop microscopic traffic simulation models that were used to assess traffic processes of emergency evacuations of nuclear power plant sites involving MTC. A recently developed model to represent MTC was integrated into the simulation to quantify its impact on clearance time and other operational parameters. The results of this effort showed that in rural or less congested urban areas clearance times experienced no significant benefit from the application of MTC. Conversely, in densely populated regions clearance times increased significantly when MTC was deployed. This suggested that for congested urban areas, with closely spaced intersections, the characteristically long cycle lengths associated with MTC resulted in significant queues. These queues propagated upstream, interfering with traffic operations at neighboring intersections and bottleneck points within the network. This, in turn, triggered even more queues and, ultimately, led to localized gridlock. From the perspective of police officers, longer cycle lengths result in fewer phase changes and less lost-time at the intersection. As such, the officer is incentivized to extend green times and cycle lengths as long as possible. What the officer cannot see, however, is the effect of such actions on queue formation at upstream intersections.